A multiscale approach for stable relaxation parameter values in lattice Boltzmann simulations of heat and mass transport in porous media. (3rd August 2022) - Madhavan, Jithin; Das, Malay K.; De, Ashoke
Abstract: Present work proposes a multiple time-scale lattice-Boltzmann method (LBM) for solving coupled convection-diffusion equations with large variation in diffusion coefficients. The key to the proposed approach is to vary the computational time-step over the solution domain according to the value of the diffusion coefficient. The proposed approach removes the limited applicability of classical LBM in simulating coupled transport phenomena with high diffusivity ratios. The proposed method is also found to be very efficient in solving heat and mass transfer problems in systems involving a combination of clear and porous media. The results indicate the efficacy of the proposed method in handling coupled flow, heat and mass transport in systems where diffusion coefficients values vary over several orders of magnitude.